Effects of facial color on the subliminal processing of fearful faces. (3rd December 2015) - Nakajima, K.; Minami, T.; Nakauchi, S.
Highlights: Using ERPs we examined the effects of facial color on processing of fearful faces. Expression × color interaction was found for N170 only in the subliminal condition. Further analyses revealed a simple main effect of color for the fearful face. Facial color affects early stage of subliminal processing of facial expression. Abstract: Recent studies have suggested that both configural information, such as face shape, and surface information is important for face perception. In particular, facial color is sufficiently suggestive of emotional states, as in the phrases: "flushed with anger" and "pale with fear." However, few studies have examined the relationship between facial color and emotional expression. On the other hand, event-related potential (ERP) studies have shown that emotional expressions, such as fear, are processed unconsciously. In this study, we examined how facial color modulated the supraliminal and subliminal processing of fearful faces. We recorded electroencephalograms while participants performed a facial emotion identification task involving masked target faces exhibiting facial expressions (fearful or neutral) and colors (natural or bluish). The results indicated that there was a significant interaction between facial expression and color for the latency of the N170 component. Subsequent analyses revealed that the bluish-colored faces increased the latency effect of facial expressions compared to the natural-colored faces, indicating that the bluish color modulated the processing of fearful expressions. We conclude that the unconscious processing of fearful faces is affected by facial color.